2018
DOI: 10.1080/14787210.2018.1453357
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with complications/sequelae of acute and subacute haematogenous osteomyelitis: an Italian multicenter study

Abstract: AHOM and SAHOM displayed some differences, however occurrence and risk factors for complications and sequelae are similar, and the same empiric treatment might be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…In most observational studies and randomised clinical trials, oral therapy consists of high-dose cephalosporin or clindamycin [ 59 , 69 , 70 , 71 ]. Trials conducted by Peltola et al showed a failure rate under 1% at follow-up [ 64 ].…”
Section: Antinfective Treatmentmentioning
confidence: 99%
“…In most observational studies and randomised clinical trials, oral therapy consists of high-dose cephalosporin or clindamycin [ 59 , 69 , 70 , 71 ]. Trials conducted by Peltola et al showed a failure rate under 1% at follow-up [ 64 ].…”
Section: Antinfective Treatmentmentioning
confidence: 99%
“…Osteomyelitis and septic arthritis can be catastrophic causing various degree of disabilities. [3,4] Prompt diagnosis and appropriate treatment are mandatory to minimize complications including avascular necrosis, growth disturbance, pathologic fractures, deep vein thrombosis, and sepsis. [5,6] In an effort to reduce such complications, advances in imaging techniques including magnetic resonance imaging has enabled early diagnosis of osteomyelitis and septic arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…We may speculate that clinicians preferred to prescribe a third-generation cephalosporin in order to reach a larger spectrum. Indeed, a recent multicenter retrospective Italian study showed a high heterogeneity of bacteria isolated in infants and children with AHOM [11]. Moreover, in children ≥3 months of age, the total duration of the treatment was longer in most Italian centers (4–6 weeks) compared to the ESPID recommendation (3–4 weeks).…”
Section: Discussionmentioning
confidence: 99%